OPTICAL AND ELECTRICAL PROPERTIES OFPOLYVINYL-CHLORIDE (PVC) FILMS - Abdullah, Omed; Tahir, Dana; Aziz, Shuja-Aldeen (Iraqi Journal of Science, 2024)
The optical properties of the polyvinyl-chloride thin films were studied whichinclude their absorbance, transmittance, reflectance spectra, band gap, and refractiveindex, before and after annealing at T = 75οC for 24hours . The films were found toexhibit high transmittance, low absorbance and low reflectance in the visible, andnear infrared region up to 1100nm. However, the absorbance of the films was foundto be high in the ultra violet region with peak around 306nm. The dielectricconstant ε′, dielectric loss ε″, and ac conductivity of polyvinyl-chloride wereobtained at different frequencies and temperatures. The experimental results showthat ε′ and ε″ decreased with increasing frequency, which indicates that the majorcontribution to the polarization comes from orientation polarization. The value of ε′increased with increasing temperature, which is due to great freedom of movementof the dipole molecular chains at high temperature.